Reflections of a student engagement program designed and delivered by academics (Journal of Applied Learning and Teaching, 2022)
Student support programs in higher education are commonly delivered by professional institution staff who are not directly involved in students’ courses. In this paper, we report on a unique student support program within a School of Education and the perceptions of the academic staff who designed and delivered the program. Methodologically, written and spoken critically reflective encounters were used to explore dimensions of student support: connectedness, mindsets, self-management, academic capabilities, and professional identity. We perceived the program positively influenced some students in developing feelings of connectedness, building self-management skills and understanding commitment, and in establishing a foundation for a student experience that fosters a pathway towards a teaching career. Tensions were revealed relating to the ethical responsibilities of supporting all students to continue study and staff’s own personal study experiences were found, at times, to contribute to assumptions about how students should engage with study. Findings suggest that addressing student needs across the dimensions first necessitates a shared understanding of what constitutes student success and how this is interpreted within a support program. Assisting academics in gaining deeper insight and understanding of what it means to be a student, particularly an academically vulnerable student, was a benefit of the program.